Potensi Sampah Anorganik Berbahan Pvc Dengan Tambahan Nano Precipitated Calcium Carbonate Dan Plasticizer Untuk Isolator Kabel Guna Keamanan Bangunan: Potential Of Inorganic Waste Made From Pvc With Added Nano Precipitated Calcium Carbonate And Plasticizer For Cable Insulators For Building Safety - Putra, Bayu Kurnia; Aditia, Frandika Laksa; Syaifulah, Muchammad Rafi; Fairuziya, Aina Afrina; Subakti, Aditya; Ingsih, Ita Suhermin (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The issue of plastic waste, particularly PVC, has become a serious environmental concern in Indonesia due to population growth, which has led to an increase in waste volume. PVC waste is challenging to recycle and often causes environmental problems, such as flooding and fires due to electrical short circuits. This study aims to reduce PVC waste by processing it into a safer and more environmentally friendly cable insulator. The research methods include the collection, sorting, mixing, and testing of PVC waste with the addition of Nano Precipitated Calcium Carbonate (NPCC) and a plasticizer. The results indicate that the PVC waste-based cable insulator possesses adequate tensile strength and elasticity, as well as electrical resistance that meets the standards of SNI 04-6629:2011 and SPLN 42-2:1992. The conclusion of this study is that the utilization of PVC waste as a cable insulator can reduce environmental problems and improve the safety of electrical installations.